Influence Quality Service and Price on Customer Satisfaction with Customer Trust as a Moderating Variable (Case Study of Shopee Xpress Jakarta Application Customers) - Albani, Yusuf; Burhan, Aditya (Universitas Kadiri, 2025)
This study aims to analyze the effect of service quality and price on customer satisfaction of Shopee. Xpress users in Jakarta, with customer trust as a moderating variable. This study uses a quantitative approach with data collection techniques through online questionnaires to 201 respondents who have used Shopee. Xpress services more than twice. The data analysis technique uses Structural Equation Modeling with Partial Approach Least Square (PLS-SEM) through SmartPLS 4 software. The results of the study indicate that service quality and price have a positive and significant effect on customer satisfaction. Customer trust also has a significant direct effect on satisfaction, but does not significantly moderate the relationship between service quality and price with customer satisfaction. These findings emphasize the importance of improving service quality and adjusting prices that are commensurate with the value of benefits, as well as building trust as an important element in increasing customer satisfaction in digital-based delivery services.